Rho GTPases Methods and Protocols - Rivero, Francisco; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Although initially described as major regulators of cytoskeletal remodeling, Rho GTPases have been implicated in the establishment of polarity, endocytosis, vesicle trafficking, morphogenesis, cytokinesis, transcriptional activation, cell cycle progression, and apoptosis, to mention a few. In addition, Rho GTPases have acquired medical relevance because of their participation in tumorigenesis and metastasis, in cardiovascular conditions, and as targets of infectious agents. The field has broadened even more with the contribution of studies in model organisms (plants, amoebas, fungi, invertebrates), each adding a particular view to the complexity of the family and vastly enriching our perception of these important signaling components. Divided into five convenient sections, Rho GTPase: Methods and Protocols provides an historical overview of the field and an account of the phylogenetics of the Rho family, general biochemical methods, and functional assays that allow monitoring the consequences of manipulating Rho GTPases in a variety of contexts. Additionally, the volume devotes a section to advanced imaging methods and to recently developed high throughput methods, closing with techniques specifically designed for studies in selected non-mammalian model organisms. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Rho GTPase: Methods and Protocols provides techniques that are standard for researchers in the field but also includes protocols for those who, being already familiar with some of the techniques, wish to explore additional aspects.
Historical Overview of Rho GTPases -- Rho GTPases: Deciphering the Evolutionary History of a Complex Protein Family -- Biochemical Assays to Characterize Rho GTPases -- How to Analyze Bacterial Toxins Targeting Rho GTPases -- Assessing Ubiquitylation of Rho GTPases in Mammalian Cells -- Posttranslational Lipid Modification of Rho Family Small GTPases -- Analysis of the Role of RhoGDI1 and Isoprenylation in the Degradation of Rho GTPases -- A Quantitative Fluorometric Approach for Measuring the Interaction of RhoGDI with Membranes and Rho GTPases -- Rho GTPases and Cancer Cell Transendothelial Migration -- Quantitative and Robust Assay to Measure Cell-cell Contact Assembly and Maintenance -- Rho GTPase Knockout Induction in Primary Keratinocytes from Adult Mice -- Rho GTPase Techniques in Osteoclastogenesis -- Assessment of Rho GTPase Signaling During Neurite Outgrowth -- Assesment of the Role for Rho Family GTPases in NADPH Oxidase Activation -- Multiplex Imaging of Rho GTPase Activities in Living Cells -- FRET-Based Imaging of Rac and Cdc42 Activation During Fc-Receptor Mediated Phagocytosis in Macrophages -- High Throughput Flow Cytometry Bead-Based Multiplex Assay for Identification of Rho GTPase Inhibitors -- Functional Analysis of RhoGTPase Activation and Inhibition in a Bead-Based Miniaturized Format -- Use of Phage Display For the Identification of Molecular Sensors Specific for Activated Rho -- Identification of New Interacting Partners for Atypical Rho-GTPases: a SILAC-Based Approach -- Using Zebrafish for Studying Rho GTPases Signaling in Vivo -- Analysis of Rho GTPase Function in Axon Pathfinding Using Caenorhabditis elegans -- Protocol for ex vivo Incubation of Drosophila Primary Post-Embryonic Haemocytes for Real-Time Analyses -- Analysis of Rho GTPase Activation in Saccharomyces cerevisiae -- Assaying Rho GTPase-Dependent Processes in Dictyostelium discoideum -- FRAP-Based Analysis of Rho GTPase-dependent Polar Exocytosis in Pollen Tubes -- Assaying Rho GTPase-Dependent Processes in Dictyostelium discoideum -- FRAP-Based Analysis of Rho GTPase-dependent Polar Exocytosis in Pollen Tubes.
Keywords: Biochemistry; Analytical chemistry; Biochemistry, general; Analytical Chemistry